Unissued philatelic essays of Basutoland 1933, and the Lesotho crocodile stamp issues - Das, Indraneil; Bauer, Aaron M. (Chicago Herpetological Society, 2020)
The crocodile motif of the Basutoland area is discussed, especially its representation in the people's beliefs and in the philately of Lesotho